Chromosome studies in some Stevia. Cav. (Compositae) species from Southern Brazil - Frederico, Adriana P.; Ruas, Paulo M.; Marin-Morales, Maria A. [UNESP]; Ruas, Claudete F.; Nakajima, Jimi N. (Sociedade Brasileira de Genética, 1996)
Karyotypes of six species of the genus Stevia from Southern Brazil were studied, utilizing root tip metaphases. All species were diploid with 2n = 22 chromosomes. It was possible to identify each species by chromosome morphology. The basic chromosome number for Brazilian species of Stevia is X = 11. This number is also found in almost all South American species. We suggest that in Stevia there is an evolutionary trend toward chromosomal rearrangement, caused mainly by pericentric inversions. It was found that, in addition to aneuploidy and polyploidy, chromosomal rearrangements are common in the tribe Eupatorieae.
Keywords: chromosome; Stevia. Cav.; Southern Brazil